PENGARUH PERAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KEUNGGULAN SEKOLAH - Taufik Ikbal (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2021)
The role of the principal and organizational culture has a strong influence on school excellence. Principals who are professional and good organizational culture will have a positive impact and fairly basic changes in reforming the education system in schools. This study aims to determine the effect of the role of school principals on school excellence and organizational culture on school excellence in SD Muhammadiyah throughout Bandar City. Lampung. This research uses associative quantitative research with a total population of 123 teachers and a sample of 94 teachers. The data collection technique uses a questionnaire. The data were analyzed using simple linear regression analysis and multiple linear regression analysis. The results showed that the influence of the principal's role and organizational culture on school excellence was 59.4% while the remaining 40.6% was influenced by other factors. So it can be concluded that the better the role of the principal and organizational culture on school excellence, the higher the school excellence.